Does the Subspecialty of the Surgeon Performing Primary Colonic Resection Influence the Outcome of Patients With Hepatic Metastases Referred for Resection? - Wigmore, Stephen J. (1999)
OBJECTIVE: To compare resection rates and outcome of patients subsequently referred with hepatic metastases whose initial colon cancers were resected by surgeons with different specialty interests. SUMMARY BACKGROUND DATA: Variation in practice among noncolorectal specialist surgeons has led to recommendations that colorectal cancers should be treated by surgeons trained in colorectal surgery or surgical oncology. METHODS: The resectability of metastases, the frequency and pattern of recurrence after resection, and the length of survival were compared in patients referred to a single center for resection of colorectal hepatic metastases. The patients were divided into those whose colorectal resection had been performed by general surgeons (GS) with other subspecialty interests (n = 108) or by colorectal specialists (CS; n = 122). RESULTS: No differences were observed with respect to age, sex, tumor stage, site of primary tumor, or frequency of synchronous metastases. Comparing the GS group with the CS group, resectable disease was identified in 26%versus 66%, with tumor recurrence after a median follow-up of 19 months in 75%versus 44%, respectively. Recurrences involving bowel or lymph nodes accounted for 55%versus 24% of all recurrences, with respective median survivals of 14 months versus 26 months. CONCLUSION: Fewer patients referred by general surgeons had resectable liver disease. After surgery, recurrent tumor was more likely to develop in the GS group; their overall outcome was worse than that of the CS group. This observation is partly explained by a lower local recurrence rate in the CS group.